Credit Default Swaps and the Empty Creditor Problem - Bolton, Patrick; Oehmke, Martin (Review of Financial Studies, 2011)
The empty creditor problem arises when a debtholder has obtained insurance against default but otherwise retains control rights in and outside bankruptcy. We analyze this problem from an ex ante and ex post perspective in a formal model of debt with limited commitment, by comparing contracting outcomes with and without insurance through credit default swaps (CDS). We show that CDS, and the empty creditors they give rise to, have important ex ante commitment benefits: By strengthening creditors' bargaining power, they raise the debtor's pledgeable income and help reduce the incidence of strategic default. However, we also show that lenders will over-insure in equilibrium, giving rise to an inefficiently high incidence of costly bankruptcy. We discuss a number of remedies that have been proposed to overcome the inefficiency resulting from excess insurance.